2001
DOI: 10.1002/ajmg.10122
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms of methylenetetrahydrofolate reductase (MTHFR) and methionine synthase reductase (MTRR) in ethnic populations in Texas; a report of a novelMTHFRpolymorphic site, G1793A

Abstract: The importance of hyperhomocysteinemia, birth defects, and vascular diseases has been the subject of intense investigations. The polymorphic MTHFR mutations (C677T and A1298C) cause mild hyperhomocysteinemia, especially in homozygotes for C677T, but also in compound heterozygotes for C677T/A1298C. The subject of this report is the frequency of the polymorphic mutations in the MTHFR gene C677T, C1298A, and newly discovered mutation G1793A, as well as the association with MTRR polymorphic site A66G in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

20
129
6
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(158 citation statements)
references
References 44 publications
(64 reference statements)
20
129
6
3
Order By: Relevance
“…However, the combined heterozygosity for both C677T and A1298C mutations resulted in significant reduction of the MTHFR enzyme activity and plasma homocysteine elevations (van der Put et al, 1998). We do not know at this point about whether or not other recently discovered mutations such as G1793A mutation in the MTHFR gene (Rady et al, 2002), D919G mutation in methionine synthase gene (Chen et al, 2001), A66G mutation in methionine synthase reductase gene (Gaughan et al, 2001), G80A mutation in the RFC-1 folate transport protein gene might have played a role in the interaction of vitamin B status and homocysteine levels in our study subjects (Chango et al, 2000).…”
Section: Discussionmentioning
confidence: 84%
“…However, the combined heterozygosity for both C677T and A1298C mutations resulted in significant reduction of the MTHFR enzyme activity and plasma homocysteine elevations (van der Put et al, 1998). We do not know at this point about whether or not other recently discovered mutations such as G1793A mutation in the MTHFR gene (Rady et al, 2002), D919G mutation in methionine synthase gene (Chen et al, 2001), A66G mutation in methionine synthase reductase gene (Gaughan et al, 2001), G80A mutation in the RFC-1 folate transport protein gene might have played a role in the interaction of vitamin B status and homocysteine levels in our study subjects (Chango et al, 2000).…”
Section: Discussionmentioning
confidence: 84%
“…Different studies have been conducted to determine the frequency of the C677T and A1298C polymorphisms in various populations around the world, and the results are as varied as the populations studied (Rosenberg et al, 2002;Rady et al, 2002;Esfahani et al, 2003). For the 677TT genotype, the highest frequency (40%) was found in Mexico and the lowest (10%) was observed in African populations (Wilcken et al, 2003;Guéant-Rodriguez et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The heterozygous form is present in 18 to 21.6% of African Americans and 41 to 43% of Caucasians. 24,25 The prevalence of MTHFR1298 homozygous is 2-4% in African Americans and 9-12.6% in Caucasians and the heterozygous frequency is 27-30% in African Americans and 43.6-47% in Caucasians. 24,25 The role of heterozygous MTHFR mutations is not clear; however, the homocysteine levels also increase in the heterozygous state, suggesting the possibility of increased risk for thrombosis.…”
Section: Introductionmentioning
confidence: 99%
“…24,25 The prevalence of MTHFR1298 homozygous is 2-4% in African Americans and 9-12.6% in Caucasians and the heterozygous frequency is 27-30% in African Americans and 43.6-47% in Caucasians. 24,25 The role of heterozygous MTHFR mutations is not clear; however, the homocysteine levels also increase in the heterozygous state, suggesting the possibility of increased risk for thrombosis. In addition, the combined heterozygosity of MTHFR 677 and 1298 increases homocysteine levels significantly and it has been suggested that this is a possible important risk factor.…”
Section: Introductionmentioning
confidence: 99%